AB0136 Induction of reg ia, a new auto-antigen in sjögren's syndrome patients, in salivary duct epithelial cells by interleukin-6 and -11. (23rd January 2014) - Fujimura, T.; Fujimoto, T.; Itaya-Hironaka, A.; Miyaoka, T.; Yoshimoto, K.; Sakuramoto-Tsuchida, S.; Yamauchi, A.; Tsujinaka, H.; Tanaka, Y.; Takasawa, S.
Abstract : Background: The regenerating gene, Reg, was originally isolated from a rat regenerating islet cDNA library, and its human homologue was named REG Iα . Reg gene product acts as a growth factor and is important for various inflammatory diseases. Sjögren's syndrome (SS) is chronic autoimmune disease characterized by inflammation of salivary and lacrimal glands, and local or systemic overexpression of pro-inflammatory cytokines is involved with the pathogenesis. Recently, we and others reported that REG Iα mRNA as well as its product (REG Iαprotein) were overexpressed in ductal epithelial cells in the minor salivary glands (MSG) of SS patients (1, 2 ). Furthermore, auto-antibodies against REG Iαwere found in SS patients and the anti-REG Iα auto-antibody positive group showed significant lower saliva secretion (2). Although some correlations between expressions of REG family genes and cytokines were reported (2), which cytokine is responsible for REG Iα expression in MSG has been elusive. Objectives: This study was undertaken to elucidate the role of cytokines for induction of REG Iα in salivary glands of Sjögren's syndrome patients. We examined which cytokines are responsible for REG Iα transcription in salivary ductal epithelial cells. Methods: Human REG Iα promoter (-1190/+26) was inserted upstream of a luciferase reporter gene in pGL3-Basic vector. The promoter plasmid was introduced by lipofection into A5 rat salivary ductal cells. After 6 hours, the cells were treated with interleukin (IL)-6 (0.2-2000 ng/ml), IL-8 (100 nM), IL-11 (0.1-1000 ng/ml), IL-22 (10 ng/ml), interferon (IFN)-β (1, 500 units/ml), and combination of them. After further 24 hour, the cells were harvested and transcriptional activity of REG Iα was measured by luciferase assay. Results: Treatment with neither IL-8, IL-22, nor IFN-β changed the transcriptional activity of REG Iα in A5 salivary ductal cells. We found that IL-6 and IL-11 significantly enhanced the REG Iα promoter activity and that the promoter was most activated by the treatment with 200 ng/ml IL-6 and 10 ng/ml IL-11, respectively. To identify the regions necessary for activation of REG Iα promoter by IL-6 or IL-11, progressive deletions of the REG Iα promoter were performed. The deletion down to position -462 did not alter significantly the expression of the reporter gene induced by IL-6 or IL-11. Progressive deletion to position -168 resulted in a gradual decrease of luciferase activity without altering the potent inducibility by IL-6 or IL-11, but an additional deletion to -67 caused a loss of inducibility. Combined addition of IL-6 and IL-11 did not show further activation of the promoter. Conclusions: The present study showed that REG Iα transcription in A5 salivary ductal cells was stimulated by IL-6 or IL-11, and that the effects of IL-6 and IL-11 were not synergistic, suggesting the signaling mechanism to activate REG Iα promoter is the same. It also suggested that overexpression of REG Iα protein in salivary ductal cells is dependent on IL-6 or IL-11 and that the IL-6/IL-11-dependent REG Iαinduction pathway may play an important role in the pathogenesis of SS. References: Kimura T et al. Clin Exp Immunol 2009;155:16-20. Yoshimoto K et al. Ann Rheum Dis 2011;70(suppl 3):93. Disclosure of Interest: None Declared